MODERN TRENDS IN HEALTH STATE OF PRE-CONSCRIPTION ADOLESCENTS IN BASHKORTOSTAN REPUBLIC - R.K. Khidiyatullina; V.A. Malievskiy ("Paediatrician" Publishers LLC, 2010)
There is a stable trend to decrease of adolescents' fitness to military service during last ten years. Authors analyzed modern tendencies in health state of youths by evaluation of State Statistics of Bashkortostan Republic in 1999-2008. Analysis showed that there is a trend to worsening of health state in youths 15-17 years old: common morbidity increased up to 30,8%, morbidity with diagnosis determined for the first time - up to 30,5%, coverage with prophylactic medical examination - up to 19,4%. There is significant growth of tumors detection (5,1 times higher), congenital malformations (3,1 times higher), diseases of musculoskeletal system and connective tissue (2,9 times higher). Common level of disability decreased up to 13,9%, initial disability - up to 30,2%. Taking into account growth of morbidity, it can be described by early diagnostics of diseases and timely administration of rehabilitation measures. Conversion of medical service of adolescents into pediatric area favored to improvement of youth's diagnostics and treatment. Key words: adolescents, health state, morbidity, disability. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(3):13-20)